Effects of feeder design (conventional dry feeder, dry shelf-feeder, and wet/dry shelf-feeder) on finishing pigs - N Amornthewaphat; Joe D Hancock; Keith C Behnke; Leland J McKinney; C W Starkey; D J Lee; C L Jones; J S Park; D W Dean (Kansas Agricultural Experiment Station Research Reports, 2000)
Pigs fed from wet/dry shelf-feeders had 6.8% greater ADG compared to those fed from dry shelf-feeders and used 18.3% less water than those fed from conventional feeders.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Feeder design; Wet/Dry feeder; Finishing pigs